Factors Affecting the Service Quality Standards at the International Airports When Viet Nam Integrates TPP: A Study at Tan Son Nhat Airport, Ho Chi Minh City, Vietnam. - Phi Hoang, Tran; Minh Thu, Dang; Thu Ha, Nguyen; Kim Quy, Huynh (British Journal of Marketing Studies, 2016)
The results this study was to identify and analyze the factors the service quality standards at the Tan Son Nhat International airport according to 39 criteria following the International Association of Aviation standards. Qualitative and quantitative research methods were combined to conduct 575 passengers with 39 observed variables (the International Association of Aviation standards) to determine the factors affecting the service quality standards at the Tan Son Nhat International airport. The study results showed that 05 factor group is influenced (1) Competence, (2) Responsiveness, (3) Access, (4) Tangibles, (5) Reliability. The objects of the findings are as follows: First, to identify the factors that affect the service quality standards at the Tan Son Nhat international airport; Second, to determine the prior order of the impact degree of factors on affecting the service quality standards at the Tan Son Nhat international airport; Third, to propose solutions for service quality at Tan Son Nhat international airport following international standards in the trend of international integration.